(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2010)
A vital aspect of democracy is the ability of individual citizens to engage in knowledge creation and evaluation in a critical manner. In today’s controversy - and information-rich society developing one’s own beliefs and values, evaluating a constantly growing body of new knowledge, and having an understanding of current politics is becoming an increasingly complex and demanding challenge. In this context, education for citizenship is an important undertaking to provide individuals with skills, values, knowledge, and beliefs needed to successfully participate in democratic processes and to foster a culture of active civic engagement.